Normal range of facial asymmetry in spherical coordinates: a CBCT study - Yoon, Suk-Ja (Korean Academy of Oral and Maxillofacial Radiology, 2013)
PURPOSE: This study aimed to measure the bilateral differences of facial lines in spherical coordinates from faces within a normal range of asymmetry utilizing cone-beam computed tomography (CBCT). MATERIALS AND METHODS: CBCT scans from 22 females with normal symmetric-looking faces (mean age 24 years and 8 months) were selected for the study. The average menton deviation was 1.01±0.66 mm. The spherical coordinates, length, and midsagittal and coronal inclination angles of the ramal and mandibular lines were calculated from CBCT. The bilateral differences in the facial lines were determined. RESULTS: All of the study subjects had minimal bilateral differences of facial lines. The normal range of facial asymmetry of the ramal and mandibular lines was obtained in spherical coordinates. CONCLUSION: The normal range of facial asymmetry in the spherical coordinate system in this study should be useful as a reference for diagnosing facial asymmetry.